The pharmacy practice of community pharmacists in Turkey [Türkiye'de serbest eczacıların eczacılık uygulamaları] - AKICI, AHMET (Marmara University, 2010)
Good pharmacy practice in community pharmacies (CP) is essential in promoting the rational use of drugs (RUD). The aim of this study was to evaluate the quality of pharmacy practice in CP according to RUD principles. The following data were a part of an interventional study in which 84 community pharmacists in the Umraniye district of Istanbul were evaluated by face to face interviews and an unannounced simulated case scenario in 2002. The average dispensing time, dispensing practice, and adequate labelling were evaluated as rationality indicators. Our results showed that 32% of the pharmacists were not present in their pharmacies during the simulation studies. Only 40.5% of the prescriptions were dispensed by the pharmacists. Forty four percent of the pharmacy employees had no more than a primary school degree. Half of the patients applying to a pharmacy had no prescription. The average dispensing time for a single drug was 149 seconds in simulated cases although the pharmacists declared 287 seconds in the questionnaires. All pharmacists reported that they explained to the patients how to administer their drugs but only 43% of the prescriptions were adequately labelled and only 6.5% included a verbal warning by the dispensers of possible interactions. In conclusion, good pharmacy practice was poorly applied in CP in the selected district of Istanbul. Since most patients consulted a pharmacist for their medication (with or without a prescription), it seemed that continuing education would be essential for pharmacists and pharmacy employees in promoting RUD.
Keywords: Community pharmacist; Dispensing score; Dispensing time; Pharmacy practice; Prescription; Rational use of drug